The Effectiveness of Dhikr Therapy as a Non-Pharmacological Intervention to Reduce Anxiety in the Elderly: Literature Review - Dwi Widyastuti; Bachtiar Safrudin; Fajar Nastangin; Dyah Faramitha; Alia Wardani; Safitri Indriyani Sari; Ridwan Maalik Yuwanda; Ikalia Ulandari; ⁠Wanda Priskyani; Imellia Harmoni Syahputri; Aliyah Nur Aini; ⁠M. Ananta Tri Purwandy (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Anxiety is one of the most common psychological problems experienced by the elderly, influenced by physical decline, chronic illness, and reduced social support. Spiritual interventions, such as dhikr therapy, are increasingly considered as complementary strategies to improve psychological well-being. This study aims to systematically review the effectiveness of dhikr therapy as a non-pharmacological intervention in reducing anxiety among the elderly. Method: A systematic literature review was conducted using the PRISMA approach. Articles were searched through Google Scholar, PubMed, ScienceDirect, and Publish or Perish with the keywords “dzikir therapy,” “elderly,” and “anxiety reduction.” Inclusion criteria were journal articles in English or Indonesian, published in the last five years, with clear methodology. Fourteen studies were included in the analysis. Result: Most studies employed quasi-experimental and pre–posttest designs with samples ranging from 10 to 50 elderly participants. The findings consistently demonstrated that dhikr therapy effectively reduced anxiety levels, improved psychological well-being, self-esteem, sleep quality, and overall quality of life. In addition, dhikr therapy contributed to better blood pressure control and reduced depression in elderly with comorbid conditions. Conclusion: Dhikr therapy is an effective, simple, and low-cost non-pharmacological intervention to reduce anxiety and enhance mental health among the elderly. Further studies with larger sample sizes, randomized controlled designs, and physiological measurements are recommended to strengthen the evidence base.